A Rare Case Report: Stroke Infark In A 5 Years Old Children with Suspected Moya-Moya Disease - Zakki K, Ahmad; Ganda Septianda H (Jurnal Kesehatan Masyarakat Indonesia (JKMI), 2026)
Ischemic stroke in children is extremely rare, with an incidence rate of approximately 1.0-2.0 per 100,000 children annually in Western countries. The highest incidence occurs in infants and children under 5 years, with a higher prevalence among males than females and among Black and Asian children than White children. Ischemic stroke is commonly associated with arteriopathy, particularly moyamoya disease. A 5-year-old male presented to the Emergency Department with weakness of the right limbs for 1 day, starting in the morning upon waking, accompanied by left-sided facial drooping and slurred speech. Vital signs were normal, general physical examination was unremarkable, with motor strength 3/5 in the right arm and 2/5 in the right leg. Laboratory results were normal, and CT scan revealed focal ischemia in the left lentiform nucleus. Acute stroke symptoms in children are similar to those in adults, commonly presenting with hemiparesis, hemifacial weakness, and speech or language disturbances. Pediatric ischemic stroke often has uncertain risk factors, including moyamoya disease, characterized by chronic, progressive stenosis of the distal internal carotid artery and proximal middle cerebral artery. Neuroimaging is crucial for diagnosis, with CT scans of the head being essential but limited in detecting acute ischemia, necessitating MRI. Conventional angiography remains the gold standard for cerebrovascular imaging, defining specific arteriopathy. This patient underwent a head CT scan revealing left lentiform nucleus ischemia and was referred to PON Hospital for MRI and further management. The diagnosis of stroke in children is primarily based on clinical presentation and radiological findings, allowing for targeted management given the heterogeneous etiology.